Prevalence and associated factors of metabolic-associated fatty liver disease in overweight Finnish children and adolescents - Riekki, Hanna; Aitokari, Linnea; Kivelä, Laura; Lahti, Siiri; Hiltunen, Pauliina; Vuorela, Nina; Huhtala, Heini; Lakka, Timo A.; Kurppa, Kalle (Frontiers in Endocrinology, 2023)
Introduction: Data on the prevalence of pediatric fatty liver disease remain limited, partly due to challenges in diagnosis. A novel concept of metabolic-associated fatty liver disease (MAFLD) makes it possible to establish the diagnosis in overweight children with sufficiently elevated alanine aminotransferase (ALT). We investigated the prevalence, risk factors, and metabolic co-morbidities of MAFLD in a large pediatric cohort. Methods: Data on 703 patients aged 2-16 years examined due to overweight in 2002-2020 were collected. MAFLD was here defined as ALT >2x reference n overweight children. Patients with MAFLD and without it were compared, and subgroup analyses were conducted among boys and girls. Results: Median age was 11.5 years, and 43% were girls. Altogether 11% were overweight, 42% obese and 47% severely obese. Abnormal glucose metabolism was present in 44%, dyslipidemia in 51%, hypertension in 48% and type 2 diabetes (T2D) in 2%. Prevalence of MAFLD was 15% (boys 18%, girls 11%; p=0.018), peaking in girls at early puberty and increasing in boys with age and puberty. No significant change occurred during the 2000s. Associated factors in boys were T2D (OR 7.55, 95%CI 1.23-46.2), postpubertal stage (5.39, 2.26-12.8), increased fasting insulin (3.20, 1.44-7.10), hypertriglyceridemia (2.97, 1.67-5.30), hyperglycemia (2.88, 1.64-5.07), decreased high-density lipoprotein (HDL) cholesterol (2.16, 1.18-3.99), and higher body-mass-index (1.01, 1.05-1.15), and in girls T2D (18.1, 3.16-103), hypertriglyceridemia (4.28, 1.99-9.21), and decreased HDL (4.06, 1.87-8.79). Conclusions: Prevalence of MAFLD was 15%, with no significant increase in the 2000s. The condition was associated in general with male gender, puberty stage and disturbances in glucose and lipid metabolism, and higher age and BMI in boys.